The crypto world trades at tea time: intraday evidence from centralized exchanges across the globe - Alexander Brauneis; Roland Mestel; Erik Theissen (Review of Quantitative Finance and Accounting, 2024)
It is a stylized fact that trading activity, volatility and liquidity in equity and other financial markets follow specific intraday patterns. These patterns are to a large extent determined by institutional features such as exchange trading hours or batch settlement procedures. We analyze the intraday patterns that emerge when these institutional constraints are absent. We compile a large sample of 1940 currency pairs traded on 38 cryptocurrency exchanges located on five continents. These exchanges operate 24~h a day, seven days a week, and settle trades instantly. We find that there are pronounced time-of-day patterns in trading activity, volatility and liquidity. These patterns are remarkably similar across exchanges, time zones and cryptocurrency pairs. Specifically, trading activity, volatility and illiquidity all peak between 16:00 and 17:00 Coordinated Universal Time (UTC), i.e. during U.K. tea time. We find that characteristics of the exchanges (such as their locations) and of the traded currency pairs (e.g. whether two pairs share a common currency) explain some, but not all of the commonality in intraday patterns.
Keywords: G12; G14; 330; Cryptocurrencies; Seasonalities; Time-of-the-day patterns; Liquidity